2022
DOI: 10.3389/fncir.2022.876789
|View full text |Cite
|
Sign up to set email alerts
|

Future research directions to identify risks and mitigation strategies for neurostructural, ocular, and behavioral changes induced by human spaceflight: A NASA-ESA expert group consensus report

Abstract: A team of experts on the effects of the spaceflight environment on the brain and eye (SANS: Spaceflight-Associated Neuro-ocular Syndrome) was convened by NASA and ESA to (1) review spaceflight-associated structural and functional changes of the human brain and eye, and any interactions between the two; and (2) identify critical future research directions in this area to help characterize the risk and identify possible countermeasures and strategies to mitigate the spaceflight-induced brain and eye alterations.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 150 publications
0
5
0
Order By: Relevance
“…A recent report of a NASA-ESA expert group ( Seidler et al, 2022 ) suggested the administration of standardized core measurements in both space and space analog studies to gain more insight into the effect of spaceflight on human brain, eye, and behavior. Therefore, they suggest including the same set of ocular measurements, up-to-date MRI protocols, cognitive and operational performance measurements, along with sensorimotor measures in future studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent report of a NASA-ESA expert group ( Seidler et al, 2022 ) suggested the administration of standardized core measurements in both space and space analog studies to gain more insight into the effect of spaceflight on human brain, eye, and behavior. Therefore, they suggest including the same set of ocular measurements, up-to-date MRI protocols, cognitive and operational performance measurements, along with sensorimotor measures in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, they suggest including the same set of ocular measurements, up-to-date MRI protocols, cognitive and operational performance measurements, along with sensorimotor measures in future studies. For standardized cognitive measurements, Seidler et al (2022) recommend NASA Cognition test battery ( Basner et al, 2015 ; Moore et al, 2017 ), the ROBoT-r tasks ( Ivkovic et al, 2019 ), along with the flight-certified Spatial Cognition test battery to be assessed “at least twice pre-flight, once early in-flight, once mid in-flight, once late in-flight, and twice post-flight. The pre- and postflight performance assays should be performed on the same day, or as near to the time of the MRI scan as possible, to support the interpretation of the functional and structural imaging data.”…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, use of artificial gravity can alleviate some of the neural changes occurring as a result of the bedrest analog condition [ 90 ]. In order to mitigate the impact of space-flight-induced changes to brain functioning, will require the development of effective countermeasures [ 91 , 92 ] and tools to detect subtle changes [ 93 ], which will require interventions, or biomarker approaches, that could potentially detect the onset of a process that could have a clinical impact [ 94 , 95 , 96 ]. Whether such functional and structural changes are reversible after chronic exposure in deep space, and whether they are associated with epigenetic alterations, remains to be determined.…”
Section: Responses Of Humans To Space Flight and Living In Leomentioning
confidence: 99%
“…Despite the clear impact of spaceflight on the central nervous system, results regarding spaceflight-related cognitive symptoms are mixed: while some studies report cognitive deficits, such as disturbed visuospatial performance 7 9 , others failed to demonstrate significant changes in cognitive performance (for reviews see 1 , 10 , 11 ). The reason behind inconsistent results includes low sample sizes and relatedly low statistical power, high variation in cognitive test batteries and targeted cognitive domains, and lack of more controllable settings, such as ground-based analogs 1 , 12 ).…”
Section: Introductionmentioning
confidence: 99%